PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING UNTUK MENINGKATKAN KETERAMPILAN MEMBACA AL-QURAN PADA SANTRI DI TPA RAUDHATUL QURAN ACEH BESAR - Muzdhalifah, Suci Firly; A. Samad, Sri Astuti; Yusuf, Irwandi; Mashuri, Mashuri; Suriana, Suriana (FISIP Universitas Malikussaleh, 2025)
This study reveals teachers' innovation in teaching ikhfa material using the Problem-Based Learning model, significantly enhancing students' understanding of tajweed and critical thinking skills. The problem-based learning model is one of the appropriate strategies in improving the learning process, including learning the science of recitation, especially the law of ikhfa'. Ikhfa' legal material is very important to study, because it has difficulties in pronouncing it. The research question is how to apply the problem based learning model to ikhfa' legal material? How do students' Al-Qur'an reading skills improve after implementing the problem based learning model on ikhfa' legal material? The method used in this research is Classroom Action Research (PTK) which consists of 2 cycles and each cycle consists of planning, implementation, observation and reflection stages. The research results found that in cycle I, Ustadzah's activities showed results of 73% in the good category and experienced an increase in cycle II with a score of 93% in the very good category. Student activities in cycle I got a percentage score of 72% in the good category and experienced an increase in cycle II with a percentage score of 94% in the very good category. The results of improving students' Al-Qur'an reading skills after implementing the problem based learning learning model on ikhfa' legal material in cycle I got an average score of 53.2 with the less successful category and experienced an increase in cycle II with an average score of 83.31 with the good category of success criteria. The application of the problem based learning model can improve the skills of reading the Al-Qur'an on Ikhfa' material for the students of TPA Raudhatul Qur'an in Aceh Besar.